The Origins of Ashkenaz, Ashkenazic Jews, and Yiddish - Das, Ranajit; Wexler, Paul; Pirooznia, Mehdi; Elhaik, Eran (Frontiers in Genetics, 2017)
Recently, the geographical origins of Ashkenazic Jews (AJs) and their native language Yiddish were investigated by applying the Geographic Population Structure (GPS) to a cohort of exclusively Yiddish-speaking and multilingual AJs. GPS localized most AJs along major ancient trade routes in northeastern Turkey adjacent to primeval villages with names that resemble the word “Ashkenaz.” These findings were compatible with the hypothesis of an Irano-Turko-Slavic origin for AJs and a Slavic origin for Yiddish and at odds with the Rhineland hypothesis advocating a Levantine origin for AJs and German origins for Yiddish. We discuss how these findings advance three ongoing debates concerning 1) the historical meaning of the term “Ashkenaz;” 2) the genetic structure of Ashkenazic Jews and their geographical origins as inferred from multiple studies employing both modern and ancient DNA and an original ancient DNA analysis; and 3) the development of Yiddish. Due to the rising popularity of geo-localization tools to address questions of origin we briefly discuss the advantages and limitations of popular tools with focus on the GPS approach. Our results reinforce the non-Levantine origins of AJs.